Objectives and contents of the activities of motor expression, according to the opinion of Physical Education teachers in Chile - Alda Reyno Freundt (FEADEF, 2010)
The current research is of a descriptive - exploratory type with a transversal design and is part of the Doctoral Thesis presented in the year 2007: « Initial formation of Physical Education Teachers in Chile and Motor Expression Area Contents» The aim of the present study is to analyze the opinion regarding the objectives and contents of the Unit «Sports and Self - improvement Activities and of Motor Expression» and of «Motor Expression Activities» (MEA), given by 249 teachers of Physical Education (PE) who were working in Chile in the year 2004. A questionnaire was applied to 249 teachers who were teaching PE at high school level (10TH and 11TH grades) in different types of schools in the country. Its purpose was detecting their opinion concerning the contents and objectives of MEA. This study describes the answers given by the teachers in the MEA questionnaire. The results were stratified by gender, according to the targets stated in this investigation. The general conclusion of this analysis indicates that in the surveyed teachers as well as in the Ministry of Education program there is a confusion in relation to what is understood by Content and Agent in Physical Education. Teachers apply Agents such as Athletics, Folklore and Dance, leaving aside bodily expression and rythmnic gymnastics.Theachers declare as an objective «To promote the care of body and health». In this way they fullfil their commitment to the «Sports Unit as well as to activites of self improvement and motor expression» it ought to be «Allow the student to express and communicate througt body and movement».